Performance comparison of (Diff-FH NEMO) scheme in IPv6-based network mobility - Hussein, Loay F.; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Zeki, Akram M. (IEEE, 2016)
Quality of Service (QoS) is defined as the capability of network elements (e.g. application, host and router) to provide some sort of assurance and service differentiation for consistent network data delivery. Recently, Internet Engineering Task Force (IETF) has introduced Network Mobility Basic Support (NEMO BS) protocol (RFC 3963) to address the challenges of the entire network mobility (such as the movements of trains, buses, ships and aircrafts). However, NEMO BS is designed without QoS support in mind. Similar to MIPv6, it can hardly offer same level of services (i.e. Best-Effort) to all the users without obligation to the applications needs. This poses a problem to real-time applications that required certain level of QoS commitment. Moreover, delays in data delivery, packet loss and higher signaling overheads are likely to transpire because of suboptimal routing and multiple encapsulations of data packets. Incorporating QoS with mobility support seems to be needed to fulfill the necessity of users in mobile network. This paper proposes a new scheme that deploys Differentiated Service (DiffServ) QoS-based model to achieve smooth delivery of real-time traffic in heterogeneous mobile networks. Furthermore, the proposed scheme uses the mechanisms of Fast Hierarchical Mobile IPv6 (FHMIPv6) to reduce location update signaling issues, since the MR doesn’t concern about local and global movement. It also conquers the weakness of NEMO inefficient routing by utilizing the methodology of MIPv6 route optimization to bypass the HA and catering optimal path. The feasibility of the proposed scheme is evaluated using Network Simulator (NS-2). The performance of proposed scheme is benchmarked with the standard NEMO basic support protocol. Eventually, the obtained results reflect that the proposed scheme outperforms the standard NEMO BS protocol by diminishing the handover latency.